Paradigms of Being in Christ: A Study of the Epistle to the Philippians - Smit, Peter-Ben (The Library of New Testament Studies, 2013)
In Philippians, Paul positions himself as an example of 'being in Christ'. The way in which he does this points out that he consciously positions himself in the tradition of classical rhetoric, where the use of paradigms was a standard element in deliberative arguing. Paul describes his life as coloured by Christ in such a way that he represents Christ to the Philippians, and the response he hopes to evoke in their congregation is that of similar behaviour. In Paradigms of Being in Christ, Peter-Ben Smit combines observations on classical rhetoric, exegetical analyses of Philippians, and view